الصناعة في مدينة الكفرة (دراسة في الجغرافية الصناعية) - منصور, جاد المولى سالم (Scientific Journal of University of Benghazi, 2021)
This study dealt with industry in the city of Al-Kufra in Libya and the study aimed at highlighting existing industries, and knowing their characteristics and factors affecting them, in addition to identifying the most important problems facing the industry, the study relied on a questionnaire and personal interviews to collect data. The study concluded that most of the industries in the city are industries - small and medium – consumer. It aims to meet the needs of the local market, and the craft industries (blacksmithing, aluminum, carpentry, marble and glass) constitute the equivalent of (55.7%) of all industries, and foreign workers represent (55.8%) of the total employment, to transfer a negative impact on the localization of the industry in the city. While other factors such as motor energy play an important role in the indigenization of the industry, the lack of trained manpower and the lack of spare parts for industrial machinery are among the most important difficulties facing the industry in the city of Kufra. The study recommended the necessity of increasing the industry in quantity and quality to comply with available resources, train workers and solve road problems, marketing, and maintenance of machinery.